Corrosion durability of strain hardening fibre-reinforced cementitious composites - Ahmed, Shaikh; Mihashi, H. (Engineers Media Pty Ltd, 2010)
This paper presents some experimental results on the corrosion durability of cracked reinforced concrete beams made with plain mortar and strain hardening fibre-reinforced cementitious composites (SHFRCCs) containing polyethylene and steel-polyethylene hybrid fibres. All beams are subjected to cyclic wetting and drying using water containing 3% sodium chloride (NaCl). In addition, an external potential is also applied to the reinforcement to accelerate the corrosion. Corrosion of steel bars is monitored through a pair of sensors attached to the reinforcing bar in each beam. Test results show that beams containing SHFRCC material exhibited better corrosion protection than that of plain mortar beams. Among all specimens, beams containing hybrid steel-polyethylene fibre-reinforced SHFRCC exhibited the best corrosion protection.